A study to explore factors that influence family caregivers of patients receiving palliative care from Island Hospice to seek help at emergency unit in Harare, Zimbabwe - Tsikai, Franciscah Ndayiziveyi (Department of Public Health and Family Medicine, 2018)
Background: This study investigated the factors that influence family caregivers of patients receiving palliative care from Island Hospice to seek help at emergency unit. The study was conducted at Island Hospice Service in Harare, Zimbabwe where Palliative care has been practiced in Zimbabwe since 1979 mainly using the home-based care model where patients are cared for by family caregivers with the support of the palliative care teams. Aim:To explore and understand issues that influence family caregivers at Island Hospice to seek help at emergency units for patients who are terminally ill. Method: This was a phenomenological study using semi-structured qualitative interviews with fifteen adult family caregivers who were the main carers of Island Hospice patients who presented at the emergency unit during the January to September 2015 period. Data were collected in Shona language using semi structured digitally recorded interviews. Data analysis through identifying themes that emerged from the transcripts. Results: Family caregivers reported the need for availability of palliative care medicine and other resources in the home setting. The family caregivers reported the need to be given information regarding the patient's diagnosis and prognosis as that would prepare them emotionally. They described challenges as pressure from relatives, witchcraft issues as well as lack of practical skills in providing care. Conclusion Considering the lack of resources and support the respondents do not support the idea of home deaths, they would rather send patients to the emergency rooms. A more organized end of life care and support for family caregivers and patients could be instituted by the hospice organization.